1999
DOI: 10.1542/peds.103.2.e18
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Manifestations of Childhood Shigellosis: Prevalence, Risk Factors, and Outcome

Abstract: ABSTRACT. Background and Objective. Alterations in consciousness, including seizures, delirium, and coma, are known to occur during Shigella infection. Previous reports have suggested that febrile convulsions and altered consciousness are more common during shigellosis than with other childhood infections. Those reports, however, have been from locations where S dysenteriae type 1 was not common, thus making it difficult to assess the specific contribution that S dysenteriae type 1 infection, and Shiga toxin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 30 publications
5
36
1
7
Order By: Relevance
“…Our observation of higher deaths in children with Shigella encephalopathy compared to those without encephalopathy is consistent with previous observations [5,10,11,28]. Although, overall case-fatality-rate among hospitalized shigellosis children reduced to <1% especially due to several non-specific interventions such as measles vaccination, vitamin A supplementation, and improved nutrition [29], the higher deaths despite the non-specific interventions in children having Shigella encephalopathy might be due to increased disease severity of such children.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observation of higher deaths in children with Shigella encephalopathy compared to those without encephalopathy is consistent with previous observations [5,10,11,28]. Although, overall case-fatality-rate among hospitalized shigellosis children reduced to <1% especially due to several non-specific interventions such as measles vaccination, vitamin A supplementation, and improved nutrition [29], the higher deaths despite the non-specific interventions in children having Shigella encephalopathy might be due to increased disease severity of such children.…”
Section: Discussionsupporting
confidence: 93%
“…It has been associated with a higher rate of deaths [810]. The most common manifestations of Shigella encephalopathy are seizure, altered consciousness and coma [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, disseminated intravascular coagulation with consumption of coagulation factors can be present in S. dysenteriae 1-associated HUS cases but is rare with STEC (527). Further shigellosis complications include septicemia and neurological disorders, such as encephalopathy and seizures (528,529). Incidences of postinfectious irritable bowel syndrome after Shigella infection have also been reported (530).…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…In a previous study on childhood shigellosis, being unconscious or having seizures was strongly associated with death, but it is unclear if seizures are simply a marker for more severe disease or seizures actually contribute to death. 10 A number of studies have reported lethal toxic encephalopathy due to shigellosis in the past few years. 2,3,7,9,11 One study reported three cases aged 9e11 years who showed a typical encephalopathic clinical and pathological pattern due to S. flexneri.…”
Section: Discussionmentioning
confidence: 99%